Takhrij and Syarah Hadith of Agrotechnology Utilization of Empty Land - Wifia Kalista Dianty; Wahyudin Darmalaksana; Gustiana Isya Marjani; Jajang Supritana (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith with regard to agrotechnology. This research method is a qualitative type through literature and field studies with the takhrij and sharah hadith approaches. The results and discussion of this study indicate that the Prophet recommended the use of empty land for farming. The conclusion of this study is the importance of using vacant land for farming according to takhrij and syarah hadith.